Pengaruh Model Pembelajaran Vct (Value Clarification Technique) Terhadap Hasil Belajar Pendidikan Agama Islam Siswa Sekolah Dasar - Heny Friantary; Ade Bayu Saputra (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
Abstract: The Influence of Vct Learning Model (Value Clarification Technique) on Learning Outcomes of Islamic Religious Education in Elementary School StudentsThe Influence of VCT Learning Model on Learning Outcomes of Islamic Religious Education Students at 90 Seluma Public Elementary Schools. The purpose of this study was to determine the effect of the Value Clarification Technique learning model on the learning outcomes of Islamic Religious Education students of the 90 Seluma Public Elementary School. The type of research is quantitative research using quasi-experimental. This design uses control and experimental groups. The data collection techniques used were observation, tests and documentation. As a result, the use of the VCT learning model in the learning process greatly influences the learning outcomes of Seluma 90 Public Elementary School students. This can be seen from the tcount obtained is 5.248 while ttable = 2.042, then tcount is greater than ttable both at the 5% significance level, thus the work hypothesis in the study which states that there is an effect of the VCT learning model on learning outcomes of Islamic Religious Education. 90 Seluma Public Elementary School students can be admitted.